If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 + 65m = 1000 Solving 90 + 65m = 1000 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-90' to each side of the equation. 90 + -90 + 65m = 1000 + -90 Combine like terms: 90 + -90 = 0 0 + 65m = 1000 + -90 65m = 1000 + -90 Combine like terms: 1000 + -90 = 910 65m = 910 Divide each side by '65'. m = 14 Simplifying m = 14
| y=10x^2-200x | | 7x-22=4(8x+7) | | 6(4x+2)=3 | | 6x-4=2(x-2) | | -11.07-12.6=.33-13.1-13.65 | | (-5.5x+7)(-7)= | | 9p^2-6p+3= | | 15=6a+3 | | 6(x-12)-2=22x-138 | | 5x^3+10x+5x=0 | | 5y+10-18=2 | | 2x+27-(4x-24)=3x-27-(2x+27) | | 3p-1/4=-5/6 | | 4x+8=14-6-8x | | 5(5-4x^2)=1125 | | X^3+6x^3= | | -20-8u=-12u+20 | | 5x-7=-28 | | 9=17-x | | (2a-8b+5)-(-3a+8b-7)= | | w+20+13w=-16+10w | | 5x+9x+6=2 | | 2(9n-1)+7(n+6)=-35 | | -1.5y(2.4x)=3+1.5y | | 2x+4=(7x+6) | | 4(x-1)=-(4+4x) | | 6z*2-2z+6=0 | | 3j=j-10 | | 40=4(a-5) | | -10(x+2)=19 | | 21=17-x | | 5t-6=6t |